Outcome of treatment of intra-articular distal end radius fractures by volar locking plate versus bridging external fixator augmented by single K-wire through radial styloid - Vishal Prakash; Neelu Singh; Vinay Prabhat (International Journal of Research in Orthopaedics, 2023)
Background: Distal radius fractures are common injuries occurring more frequently than any other fracture, and remain one of the most frequent skeletal injuries treated by orthopaedic or trauma surgeons. They are considered the most common fracture of the upper extremity. The use of percutaneous pin fixation, external fixation devices that permit distraction and palmar translation, low-profile internal fixation plates and implants, arthroscopically assisted reduction, and grafting techniques including bone-graft substitutes all have contributed to improving fracture stability and outcome. Methods: This is a prospective study consisting of 30 patients, who were treated with volar locking plate or K-wire augmented external fixation for intra-articular commented distal radius fractures (AO type C) at Rajendra institute of medical sciences between November 2020 and January 2023. The 15 patients were treated with open reduction using the volar approach and locking plate were used while 15 patients were treated with closed reduction under fluoroscopy, distraction with the external fixator (Joshi type external fixator) along with K-wire fixation for additional stability used. Result: The ORIF with plating group showed better functional outcomes in Green and O’Brien compared to ex fix group. The radiographic results in the ORIF group were more favorable than in the EF group. Conclusions: We found that both ORIF with plating and external fixation represent treatment choices for distal radius fractures. ORIF had better functional and radiological outcomes according to Green and O’Brien and Sarmiento scoring systems when compared to external fixation. ORIF had less incidence of complications compared with external fixation.